Impact of COVID-19 Pandemic on Patients with Serious Mental Illness (SMI) and Nonpsychiatric Control Subjects in Clinical Trials. - GARCIA-RADA, MARIA FE; LITMAN, ROBERT E. (Innovations in Clinical Neuroscience)
Objective: This study aimed to examine the impact of the COVID-19 pandemic on patients with serious mental illness (SMI), specifically relating to psychiatric morbidity, pandemic-induced stress, and ability to cope with pandemic-related precautionary measures, restrictions, and disruptions to daily life. Design: A cross-sectional survey study of 277 clinical trial patients was conducted. This sample included nonpsychiatric controls (n=139) and patients with a diagnosis of bipolar disorder, major depressive disorder (MDD), or schizophrenia (n=138) located at five clinical trial sites across the United States. A univariate analysis was performed to obtain general frequencies of the sample. Unpaired t-tests were used in comparing the groups on numerical variables, and analysis of variance (ANOVA) was performed to identify difierences when comparing three or more categories. Results: Patients with SMI were more likely to report wearing face masks, avoiding large gatherings, and endorsing the use of precautionary measures, despite receiving a COVID-19 vaccine (p<0.001). A total of 70.3 percent (n=97) of all patients with SMI reported experiencing at least one episode of symptom worsening, 48 percent reported experiencing suicidal ideation, and 66 percent reported a need for increased mental healthcare due to COVID-19-related distress. Patients with SMI reported higher levels of stress, compared to controls, with patients with MDD having the highest levels of stress (p<0.001). Conclusion: These findings demonstrate an increased vulnerability to symptom worsening in patients with SMI during a pandemic and suggest the need to account for pandemic-induced psychological stress in clinical trial design, subject selection, and symptoms ratings.